1997
DOI: 10.1128/mcb.17.9.5244
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gene Expression by Cyclic GMP-Dependent Protein Kinase Requires Nuclear Translocation of the Kinase: Identification of a Nuclear Localization Signal

Abstract: We recently demonstrated that cyclic GMP (cGMP)-dependent protein kinase (G-kinase) activates the human fos promoter in a strictly cGMP-dependent manner (T. Gudi et al., J. Biol. Chem. 271: [4597][4598][4599][4600] 1996). Here, we demonstrate that G-kinase translocates to the nucleus by an active transport mechanism which requires a nuclear localization signal (NLS) and is regulated by cGMP. Immunofluorescent staining of G-kinase was predominantly cytoplasmic in untreated cells, but intense nuclear staining ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
150
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(156 citation statements)
references
References 52 publications
(58 reference statements)
6
150
0
Order By: Relevance
“…The cyclic nucleotide-dependent kinases have also been shown directly to mediate some gene expression, although emphasis has been on the ability to activate the transcription factor CREB by direct phosphorylation. These studies have lead to some debate as to how the cytosolically located PKG can activate the predominantly nuclear CREB as a substrate (31,43,44). The activation of MAPKs by PKG can therefore provide an alternative mechanism by which PKG can regulate transcription without nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%
“…The cyclic nucleotide-dependent kinases have also been shown directly to mediate some gene expression, although emphasis has been on the ability to activate the transcription factor CREB by direct phosphorylation. These studies have lead to some debate as to how the cytosolically located PKG can activate the predominantly nuclear CREB as a substrate (31,43,44). The activation of MAPKs by PKG can therefore provide an alternative mechanism by which PKG can regulate transcription without nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%
“…31 Previous studies have shown that colocalization of p53, protein kinase A, and protein kinase G in the nucleus provide access for these 2 kinases to phosphorylate p53. 32,33 Because NO can induce p53 activation and nuclear localization and can activate protein kinase G through the ability to increase guanylate cyclase activity, it is reasonable to propose that the NOinduced activation of p53 is related to increased cGMP levels. At high levels of NO, it is presumed that protein kinase A can be activated by the inordinately high concentrations of cGMP produced, 6 and because the catalytic subunit of protein kinase A can translocate to the nucleus, the possibility exists that either or both protein kinases might mediate an effect of cGMP by nuclear localization and subsequent p53 activation.…”
Section: Discussionmentioning
confidence: 99%
“…At high levels of NO, it is presumed that protein kinase A can be activated by the inordinately high concentrations of cGMP produced, 6 and because the catalytic subunit of protein kinase A can translocate to the nucleus, the possibility exists that either or both protein kinases might mediate an effect of cGMP by nuclear localization and subsequent p53 activation. Furthermore, because protein kinases A and G can phosphorylate transcriptional factors related to cAMP response element binding protein, 32 other diverse effects could promote either p53-dependent or -independent increases in p21 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…In other PKGs, cGMP binding has been shown to relieve an inhibitory interaction between an amino terminal pseudosubstrate region and the kinase domain (31). cGMP binding has been shown to both activate the kinase and promote nuclear translocation of PKG 1α in mammalian cells (32). Altering key residues within either or both cGMP-binding domains (T276A and T398A) of GFP-EGL-4 led to exclusively cytosolic GFP, even after prolonged odor exposure (Fig.…”
Section: Percent Nuclear Gfp-egl-4 Per Unit Time At Each Time Interval)mentioning
confidence: 99%
“…3B). The NLS of the kinasedefective mutant should be exposed by cGMP binding (32), and yet, it is defective for nuclear entry. Since the NLS of the kinase defective mutant should be exposed by cGMP binding, the fact that we observe a partial dependence on the kinase domain indicates that nuclear translocation may be enhanced by a kinase function.…”
Section: Percent Nuclear Gfp-egl-4 Per Unit Time At Each Time Interval)mentioning
confidence: 99%